Cell surface display of palladium binding peptide on Saccharomyces cerevisiae EBY100 cells using the a-agglutinin anchor system developed for the biosorption of Pd (II). (January 2022) - Mashangoane, Boitumelo F.; Chirwa, Evans N.
Abstract: Platinum group metals (PGMs) are concentrated in the earth's core and mantle and have low natural abundances. Due to the limited availability of PGMs; their recovery and reuse from waste solutions is economically attractive. Conventional methods used for the removal of PGMs from effluents include precipitation, ion exchange, and reverse osmosis; these methods have many shortfalls and this had led to a search for new technologies for the removal of metals from effluents, one such technology is biosorption. The primary objective of this research project was to develop a genetically engineered Saccharomyces cerevisiae EBY100 strain for the biosorption of Pd(II) in aqueous solutions. The palladium binding peptide was successfully expressed on Saccharomyces cerevisiae EBY100 cells by means of cell surface display using the a-agglutinin anchor system; this was confirmed by means of DNA sequencing, flow cytometry and fluorescence microscopy. The maximum adsorption capacity of genetically transformed Saccharomyces cerevisiae EBY100 cells for Pd(II) was 125 mg/g.